Mannose receptor interacts with Fc receptors and is critical for the development of crescentic glomerulonephritis in mice - Chavele, Konstantia-Maria; Martinez-Pomares, Luisa; Domin, Jan; Pemberton, Samantha; Haslam, Stuart M.; Dell, Anne; Cook, H. Terence; Pusey, Charles D.; Gordon, Siamon; Salama, Alan D. (The Journal of clinical investigation, 2010)
Crescentic glomerulonephritis (CGN), which frequently results in acute and chronic kidney disease, is characterized by and dependent on glomerular infiltration by macrophages. The mannose receptor (MR) is a pattern recognition receptor implicated in the uptake of endogenous and microbial ligands by macrophages, mesangial cells (MCs), and selected endothelial cells. It is upregulated on alternatively activated macrophages (i.e., macrophages associated with tissue repair and humoral immunity) and involved in antigen presentation to T cells. We used the mouse model of nephrotoxic nephritis to investigate the role of MR in CGN. Our results demonstrate what we believe to be a novel role for MR in the promotion of CGN that is independent of adaptive immune responses. MR-deficient (Mr-/-) mice were protected from CGN despite generating humoral and T cell responses similar to those of WT mice, but they demonstrated diminished macrophage and MC Fc receptor-mediated (FcR-mediated) functions, including phagocytosis and Fc-mediated oxygen burst activity. Mr-/- MCs demonstrated augmented apoptosis compared with WT cells, and this was associated with diminished Akt phosphorylation. Macrophage interaction with apoptotic MCs induced a noninflammatory phenotype that was more marked in Mr-/- macrophages than in WT macrophages. Our results demonstrate that MR augments Fc-mediated function and promotes MC survival. We suggest that targeting MR may provide an alternative therapeutic approach in CGN while minimizing the impact on adaptive immune responses, which are affected by conventional immunosuppressive approaches.